Investment in education under disappointment aversion - Dan Anderberg; Claudia Cerrone (Max Planck Institute for Research on Collective Goods, 2016)
This paper develops a model of risky investment in education under disappointment aversion, modelled as loss aversion around one's endogenous expectation. The model shows that disappointment aversion reduces the optimal investment in education for lower ability people and increases it for higher ability people, thereby magnifying the investment gap between them generated by the riskiness of education. Policies aimed at influencing students' expectations can reduce early dropout.
Keywords: D03; D81; I21; 330; education; risk; disappointment aversion; endogeneous reference points